ANALISIS KUALITAS PELAYANAN, HARGA DAN FASILITAS TERHADAP KEPUASAN KONSUMEN PENGGUNA PT ROSALIA INDAH TRANSPORT (Survei pada Pelanggan PT Rosalia Indah Transport di Palur Karanganyar) - Retno Susanti, Aprilia Rintang Rositawati, Untung Sriwidodo & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
This study aims to determine the significance of the effect of service quality on customer satisfaction using bus transportation services PT Rosalia Indah Transport in Palur Karanganyar; the effect of price on consumer satisfaction that use bus transportation services PT Rosalia Indah Transport in Palur Karanganyar; the effect of the facility to the satisfaction of consumers who use bus transportation services PT Rosalia Indah Transport in Palur Karanganyar; which of the quality of service, pricing, or facilities were dominant influence on consumer satisfaction using bus transportation services PT Rosalia Indah Transport in Palur Karanganyar. The population in this study is that consumers who use bus transportation services PT Rosalia Indah Transport in Palur Karanganyar, with a sample of 70 respondents with accidental sampling technique. The technique of collecting data using questionnaires instrument through the stages of testing the validity and reliability first. Test requirements regression using classic assumption test. Data were analyzed using linear regression analysis beganda. The results showed that the quality of service significantly influence consumer satisfaction using bus transportation services PT Rosalia Indah Transport in Palur Karanganyar; prices not significant effect on customer satisfaction using bus transportation services PT Rosalia Indah Transport in Palur Karanganyar; facilities significantly influence consumer satisfaction using bus transportation services PT Rosalia Indah Transport in Palur Karanganyar; service quality is a dominant influence on the satisfaction of consumers who use bus transportation services PT Rosalia Indah Transport in Palur Karanganyar.Keywords: service quality, price, amenities, customer satisfaction.